Economic performance and the theory of the firm : the selected papers of David J Teece - Teece, David J. (Cheltenham, U.K. : Edward Elgar, 1998)
A collection of articles previously published between 1978-1997. Includes bibliographical references and index
Keywords: Economics; Industrial efficiency; Industrial organizations (Economic theory).; International business enterprises -- Management; Strategic planning; Technological innovations -- Economic aspects